1984
DOI: 10.1104/pp.74.4.1016
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Phase Behavior of Phosphatidylglycerols from Chilling-Sensitive and Chilling-Resistant Plants

Abstract: Seven major lipid classes were isolated from leaves of chilling-sensitive and chilling-resistant plants, and the temperature-dependent phase behaviors of their aqueous dispersions were studied by a fluorescence polarization method using trans-parinaric acid and its methyl ester.Phosphatidyiglycerols from the chilling-sensitive plants went In the mechanism proposed by Raison (18) and Lyons (7) for the chilling sensitivity of plants, the primary event in chilling injury is the formation ofa lipid gel phase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
2

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 22 publications
3
81
2
Order By: Relevance
“…We believe that the collapse of photosynthesis and death of fab1 plants at 2°C is caused by the increase in saturated 16:0 fatty acids and most probably by the presence of approximately 70% high-melting-point fatty acids in chloroplast PG (Wu et al, 1997). This hypothesis is consistent with the other evidence discussed above (Murata et al, 1982;Murata and Yamaya, 1984;Roughan, 1985;Murata et al, 1992;Ishizaki-Nishizawa et al, 1996). It is therefore unexpected that a further increase in chloroplast 16:0 should provide a suppressor phenotype, especially when fad5 mutant plants are themselves compromised in growth and chloroplast biogenesis at low temperature (Hugly and Somerville, 1992).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We believe that the collapse of photosynthesis and death of fab1 plants at 2°C is caused by the increase in saturated 16:0 fatty acids and most probably by the presence of approximately 70% high-melting-point fatty acids in chloroplast PG (Wu et al, 1997). This hypothesis is consistent with the other evidence discussed above (Murata et al, 1982;Murata and Yamaya, 1984;Roughan, 1985;Murata et al, 1992;Ishizaki-Nishizawa et al, 1996). It is therefore unexpected that a further increase in chloroplast 16:0 should provide a suppressor phenotype, especially when fad5 mutant plants are themselves compromised in growth and chloroplast biogenesis at low temperature (Hugly and Somerville, 1992).…”
Section: Discussionsupporting
confidence: 82%
“…One hypothesis, specific to chloroplast membranes, proposes that molecular species of chloroplast PG that contain high-melting-point fatty acids at both the sn-1 and sn-2 positions of the glycerol backbone confer chilling sensitivity on plants (Murata, 1983;Nishida and Murata, 1996). This hypothesis is supported by several lines of evidence, including the detection of L a to L b phase transitions in PG isolated from chilling-sensitive plants (Murata and Yamaya, 1984), a correlation across plant species between the proportion of high-melting-point fatty acids in PG and the degree of chilling sensitivity (Murata et al, 1982;Roughan, 1985), and evidence from transgenic plants with engineered alterations in the fatty acid composition of PG (Murata et al, 1992;Wolter et al, 1992).…”
Section: Discussionmentioning
confidence: 48%
“…In fubl plants, the proportion of fatty acids with melting points above 2OoC (16:O plus 16:l-trans plus 18:O) in phosphatidylglycerol is 69% compared with a value in wild type of 55%. The significance of this finding lies in the fact that surveys of many plant species (Murata et al, 1982;Murata and Yamaya, 1984;Roughan, 1985) have consistently found that plants containing more than 60% of these high melting point fatty acids in the leaf phosphatidylglycerol are invariably subject to damage at temperatures in the range Oo to 10°C, i.e. they are chilling-sensitive plants.…”
Section: Mutants Ofmentioning
confidence: 99%
“…One of the most enduring hypotheses in the general area of a plant's susceptibility to chilling stress proposes that the molecular species of chloroplast PG, containing a combination of saturated fatty acids (16:0, 18:0, or 16:l-truns) at both the sn-1 and sn-2 position of the glycerol backbone (high-melting-point PG molecular species), confer chilling sensitivity to plants (Murata and Yamaya, 1984;Murata et al, 1992). Although this hypothesis has been supported by a number of experimental observations, the recent characterization of the Arabidopsis f u b l mutants has provided a counterexample that demonstrates that the high-meltingpoint species of PG can have no more than a contributory effect in inducing chilling sensitivity.…”
mentioning
confidence: 99%